Nutrition and Nutritional Issues for Dancers - Monica Sousa (2013)
Proper nutrition, not simply adequate energetic intake, is needed to achieve optimal dance performance. However, little scientific research exists concerning nutrition in dance, and so, to propose nutritional guidelines for this field, recommendations need to be based mainly on studies done in other physically active groups. To diminish the risk of energy imbalance and associated disorders, dancers must consume at least 30 kcal/kg fat-free mass/day, plus the training energy expenditure. For macronutrients, a daily intake of 3 to 5 g carbohydrates/kg, 1.2 to 1.7 g protein/kg, and 20 to 35% of energy intake from fat can be recommended. Dancers may be at increased risk of poor micronutrient status due to their restricted energy intake; micronutrients that deserve concern are iron, calcium, and vitamin D. During training, dancers should give special attention to fluid and carbohydrate intake in order to maintain optimal cognition, motivation, and motor skill performance. For competition/stage performance preparation, it is also important to ensure that an adequate dietary intake is being achieved. Nutritional supplements that may help in achieving specific nutritional goals when dietary intake is inadequate include multivitamins and mineral, iron, calcium, and vitamin D supplements, sports drinks, sports bars, and liquid meal supplements. Caffeine can also be used as an ergogenic aid. It is important that dancers seek dietary advice from qualified specialists, since the pressure to maintain a low body weight and low body fat levels is high, especially in styles as ballet, and this can lead to an unbalanced diet and health problems if not correctly supervised.